The United Nations, Intelligence and Peacekeeping - Larsson,Pavel (2010)
The end of the Cold War marked the ending of an era of a bipolar rivalry, but it also brought about a new set of challenges for policymakers and national intelligence agencies. One of these new challenges is sharing sensitive information with states and actors outside comfortable alliances, whilst countering a myriad of asymmetric, often low-level type of security threats. Implementation of intelligence components in multinational peacekeeping operations has been, to say the least, troublesome. A tactical, as well as strategic component for successful conflict resolution has therefore often been jeopardized. As the international community demanded a better and more effective use of peacekeepers, grounded international relations held a firm grip on cooperation in the intelligence realm in these multinational interventions. This has led to ad hoc type of solutions, leading to poor situational awareness and support for key policymakers. This paper describes international intelligence liaison in UN-led peacekeeping operations, and the often present challenges within that multilateral context. Several missions are analyzed, as well as two cases of bilateral intelligence cooperation outside the UN realm. The conclusion is that intelligence liaison is a sensitive matter for states and that the UN organization is an unfavorable partner to deal with.
Keywords: Mearsheimer; peacekeeping; UN; liaison; intelligence; UKUSA